PENGARUH MODEL PEMBELAJARAN PENEMUAN TERBIMBING DALAM MENINGKATKAN KEMAMPUAN PENALARAN DAN SIKAP MATEMATIS SISWA - Noneng Rosmini (Universitas Pendidikan Indonesia, 2020)
This research is aimed at comparing whether students taught using guided discovery learning model perform better in mathematical reasoning and disposition. This research employed quasi-experimental design involving 62 fifth grade students from two different elementary schools in Lembang. The data were collected by utilizing a test, a questionnaire and an observation sheet. The data obtained from the test and questionnaire were analyzed statistically using t-test to see two different average values. The result of the analysis and t-test show that there were two different average scores in which the students taught using guided discovery learning model achieve higher scores in terms of mathematical reasoning and disposition compared to students taught using conventional learning model.